Sugar fuels T-cell memory. Issue 1 (January 2018) - Olivas, Joanna; Horng, Tiffany
Previous work has highlighted the role of metabolic shifts in regulating the formation of memory T cells, which are generated during a primary infection to provide long-lasting immunity. A study now shows that memory T cells rely on a gluconeogenesis–glycogenolysis cycle to provide antioxidant defence and support their survival.